Butyrate Conversion by Sulfate-Reducing and Methanogenic Communities from Anoxic Sediments of Aarhus Bay, Denmark - Derya Ozuolmez; Elisha K. Moore; Ellen C. Hopmans; Jaap S. Sinninghe Damsté; Alfons J. M. Stams; Caroline M. Plugge (Microorganisms, 2020)
The conventional perception that the zone of sulfate reduction and methanogenesis are separated in high- and low-sulfate-containing marine sediments has recently been changed by studies demonstrating their co-occurrence in sediments. The presence of methanogens was linked to the presence of substrates that are not used by sulfate reducers. In the current study, we hypothesized that both groups can co-exist, consuming common substrates (H2 and/or acetate) in sediments. We enriched butyrate-degrading communities in sediment slurries originating from the sulfate, sulfate–methane transition, and methane zone of Aarhus Bay, Denmark. Sulfate was added at different concentrations (0, 3, 20 mM), and the slurries were incubated at 10 °C and 25 °C. During butyrate conversion, sulfate reduction and methanogenesis occurred simultaneously. The syntrophic butyrate degrader Syntrophomonas was enriched both in sulfate-amended and in sulfate-free slurries, indicating the occurrence of syntrophic conversions at both conditions. Archaeal community analysis revealed a dominance of Methanomicrobiaceae. The acetoclastic Methanosaetaceae reached high relative abundance in the absence of sulfate, while presence of acetoclastic Methanosarcinaceae was independent of the sulfate concentration, temperature, and the initial zone of the sediment. This study shows that there is no vertical separation of sulfate reducers, syntrophs, and methanogens in the sediment and that they all participate in the conversion of butyrate.